2013
DOI: 10.4236/chnstd.2013.21003
|View full text |Cite
|
Sign up to set email alerts
|

Consumption Behaviours of Park Visitors and the Implications for Tourism Marketing: A Case in China

Abstract: A survey of tourists to the protected areas in the Taibai Mountain (太白山) Region of China reveals a local domestic market, dominated by students and company employees. The market is attracted by the natural beauty of the Region, but not yet focused on nature based activities in the many protected areas. Given the Region's assured tourism future based on its natural and cultural characteristics, the survey data are used to discuss strategies for development. The fundamental issue is how to design tourism product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Lamb, Hair and McDaniel (2004) have indicated that a thorough understanding of a market profile should benefit the effective promotion of a tourist product and thus effective marketing. Tourist typologies are useful in tourism planning only to the extent that they reflect tourist behaviour and the level of discomfort they bring to the receiving system (Benxiang 2013). Thus, an analysis of the demographic profile of nature-based tourists can benefit tourism marketers, especially with regard to market segmentation, product development, service quality evaluation, image development and promotional activities (Kruger, Viljoen & Saayman 2016).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lamb, Hair and McDaniel (2004) have indicated that a thorough understanding of a market profile should benefit the effective promotion of a tourist product and thus effective marketing. Tourist typologies are useful in tourism planning only to the extent that they reflect tourist behaviour and the level of discomfort they bring to the receiving system (Benxiang 2013). Thus, an analysis of the demographic profile of nature-based tourists can benefit tourism marketers, especially with regard to market segmentation, product development, service quality evaluation, image development and promotional activities (Kruger, Viljoen & Saayman 2016).…”
Section: Literature Reviewmentioning
confidence: 99%